Time to eRAASe chronic inflammation: current advances and future perspectives on renin-angiotensin-aldosterone-system and chronic intestinal inflammation in dogs and humans - Heilmann, Romy M.; Csukovich, Georg; Burgener, Iwan A.; Dengler, Franziska (Frontiers in Veterinary Science, 2023)
Chronic idiopathic intestinal inflammation is an increasing worldwide problem that affects companion animals, especially dogs, and human patients. Although these disease entities have been intensely investigated recently, many questions remain, and alternative therapeutic options are needed. Diarrhea caused by dysregulation of intestinal electrolyte transport and subsequent fluid and electrolyte losses often leads to secondary consequences for the patient. Currently, it is not exactly clear which mechanisms are involved in the dysregulation of intestinal fluid absorption, but differences in intestinal electrolyte shifts between human and canine patients suggest species-specific regulatory or counterregulatory mechanisms. Several intestinal electrolyte transporters are differentially expressed in human patients with inflammatory bowel disease (IBD), whereas there are virtually no studies on electrolyte transporters and their endocrine regulation in canine chronic inflammatory enteropathy. An important mechanism involved in regulating fluid and electrolyte homeostasis is the renin-angiotensin-aldosterone-system (RAAS), which may affect intestinal Na+ transport. While RAAS has previously been considered a systemic regulator of blood pressure, additional complex roles of RAAS in inflammatory processes have been unraveled. These alternative RAAS pathways may pose attractive therapeutic targets to address diarrhea and, thus, electrolyte shifts in human IBD and canine chronic inflammatory enteropathy. This article comparatively summarizes the current knowledge about electrolyte transport in human IBD and canine chronic inflammatory enteropathy and the role of RAAS and offers perspectives for novel therapeutic avenues.